Damage to Nursery Stock by a Rodent Nesokia indica (Gray) at Satyanarayan Forest Nursery, Dehra Dun (Uttar Pradesh) - Kumar, Sushil; Thakur, M. L. (Indian Forester, 1989)
The paper gives an account of nature and extent of damage by a species of short tailed mole rat Nesokia indica (Gray) to the nursery stock at Satyanarayan Forest Nursery, Dehra Dun. Observations on the burrows and the burrowing habits of the species are also included. This appears to be the first record of this species as a forestry pest in northern India.